تأثير بعض الملوثات الغازية الصناعية في بعض الخواص المورفوفيزيولوجية لنبات القمح الطري Triticum aestivum L. - عياش عبد الكريم; وهبي رفعات; شمالي سمر (Latakia University Journal -Biological Sciences Series, 2019)
أجري البحث على نباتات القمح التي جرى زراعتها في منطقة قريبة من معمل الأسمدة الكيميائية بمحافظة حمص – سوريا، وذلك بهدف دراسة تأثير بعض الملوثات الغازية المنبعثة من المصنع (SO2 وNO2) ودقائق الغبار الصناعي في بعض الخواص المورفوفيزيولجية لنبات القمح الطري (صنف شام 6). أظهرت النتائج أن التأثير السلبي لهذه الملوثات يتضح بشكل خاص في المنطقة القريبة من سور المعمل (60 متراً) بعد التعريض المستمر بدءاً من عمر 35 يوماً، بالنسبة لطول النبات (انخفاض بنسبة 39.16%) وبدءاً من عمر 70 يوماً بالنسبة لكمية اليخضور الكلي (انخفاض بنسبة 26.07 %)، وأن تأثير هذه الملوثات كان ولايزال واضحاً لمسافة 900 متر من سور المعمل. The study was carried out on wheat plants that were grown in the area close to the chemical fertilizer factory - Governorate Homs - Syria, in order to examine the effect of certain gaseous pollutants emitted from the factory (SO2 and NO2) and industrial dust particles in some morphophysiological properties of soft wheat plant (variety Cham 6). The results showed that the negative effect of these pollutants is particularly evident in the region near the factory wall (60 meters) after constant exposure from age 35 days for plant height (a decrease of 39.16%) and starting from age 70 days for the amount of total chlorophyll (a decrease of 26.07%). The effect of these pollutants was still clear for a distance of 900 meters from the factory wall.